Data-driven digital health technologies in the remote clinical care of diabetic foot ulcers: a scoping review - Lazarus, Joel; Cioroianu, Iulia; Ehrhardt, Beate; Gurevich, David; Kreusser, Lisa; Metcalfe, Benjamin; Nishtala, Prasad; Preatoni, Ezio; Sharp, Tamsin H. (Frontiers in Clinical Diabetes and Healthcare, 2023)
The availability and effectiveness of Digital Health Technologies (DHTs) to support clinicians, empower patients, and generate economic savings for national healthcare systems are growing rapidly. Of particular promise is the capacity of DHTs to autonomously facilitate remote monitoring and treatment. Diabetic Foot Ulcers (DFUs) are characterised by high rates of infection, amputation, mortality, and healthcare costs. With clinical outcomes contingent on activities that can be readily monitored, DFUs present a promising focus for the application of remote DHTs.Objective: This scoping review has been conducted as a first step toward ascertaining the data-related challenges and opportunities for the development of more comprehensive, integrated, and individualised sense/act DHTs. We review the latest developments in the application of DHTs to the remote care of DFUs. We cover the types of DHTs in development and their features, technological readiness, and scope of clinical testing.Eligibility criteria: Only peer-reviewed original experimental and observational studies, case series and qualitative studies were included in literature searches.. All reviews and manuscripts presenting pre-trial prototype technologies were excluded.Methods: An initial search of three databases (Web of Science, MEDLINE, and Scopus) generated 1,925 English-language papers for screening. 388 papers were assessed as eligible for full-text screening by the review team. 81 manuscripts were found to meet the eligibility criteria.Results: Only 19% of studies incorporated multiple DHTs. We categorised 56% of studies as 'Treatment-Manual', i.e. studies involving technologies aimed at treatment requiring manual data generation, and 26% as 'Prevention-Autonomous', i.e. studies of technologies generating data autonomously through wearable sensors aimed at ulcer prevention through patient behavioural change. Only 10% of studies involved more ambitious 'Treatment-Autonomous' interventions. We found that studies generally reported high levels of patient adherence and satisfaction.Our findings point to a major potential role for DHTs in remote personalised medical management of DFUs. However, larger studies are required to assess their impact. Here, we see opportunities for developing much larger, more comprehensive, and integrated monitoring and decision support systems with the potential to address the disease in a more complete context by capturing and integrating data from multiple sources from subjective and objective measurements.